History of the Giraffe Pipe locality inferred from microfossil remains: a thriving freshwater ecosystem near the Arctic Circle during the warm Eocene. (March 2023) - Siver, Peter A.; Lott, Anne Marie
Abstract: How will freshwater lakes in the Arctic respond to climate change, especially if polar amplification results in even greater warming at these northern latitudes? Deep time analogs offer opportunities to understand the potential effects of future climate warming on arctic environments. A core from the Giraffe Pipe fossil locality located in the Northwest Territories of Canada offers a window into the life of a thriving Arctic freshwater ecosystem in the Eocene during greenhouse conditions. The remains of an extensive deposit of microfossils, including photosynthetic protists (chrysophytes, diatoms, and green algae), heterotrophic protists (euglyphids, heliozoans, paraphysomonads, and rotosphaerids), and sponges, were used to reconstruct the history of the ancient waterbody. Concentrations and diversity of chrysophyte taxa were extensive throughout the core, accounting for >70% of the microfossil remains. The ratio of chrysophyte cysts to diatom valves, with a mean value near 14 throughout the core, further emphasized the dominance of the chrysophytes, and given the high diversity of taxa, the locality represents a "paleo-hotspot" for this eukaryote lineage. Based on the totality of fossil evidence, the waterbody within the Giraffe Pipe crater represented a series of relatively shallow aquatic habitats, with changing physical and chemical conditions, and varying water depths. Five major zones were identified, each found to be stable for an extended period of time, but with distinct transitions between successive zones signaling significant shifts in environmental conditions. The study provides valuable insight on how Arctic freshwater ecosystems responded to past warm climates, and to the organisms that could potentially thrive in these environments under future warming scenarios.